A population-based study of outcomes in adjuvant radiotherapy for stage II endometrial carcinoma. Issue 10 (22nd June 2022) - Moldovan, Nataliya; Lambert, Pascal; Ong, Aldrich; Altman, Alon D
Abstract : Objective: Our study aimed to analyze recurrence and survival outcomes in stage II endometrial cancer patients treated with adjuvant radiotherapy at CancerCare Manitoba, a Canadian provincial cancer program. Methods: This retrospective population-based cohort study identified all International Federation of Gynecology and Obstetrics (FIGO) 2009 stage II endometrioid type endometrial carcinoma diagnosed between January 1995 and December 2019. All patients underwent surgery followed by vaginal vault brachytherapy alone or external beam pelvic radiotherapy plus vaginal vault brachytherapy. We used Kaplan-Meier curves to describe overall survival and recurrence-free survival, and cumulative incidence to describe recurrence. Cox regression was used to predict overall survival and recurrence-free survival competing risk regression to predict recurrence. Results: A total of 121 patients were included (78 vaginal brachytherapy alone and 43 external beam pelvic radiotherapy plus vaginal brachytherapy) with a median age of 62 (range 24–85). The median follow-up was 55.2 months (range 7.1–147.9) in the vaginal brachytherapy group and 41.9 months (range 7.4–127.0) in the pelvic radiotherapy group. Lymph node dissection was performed in 79 (65.3%) patients. There were 14 (17.9%) recurrences (8 vaginal vault, 3 pelvic, 3 distant) with vaginal brachytherapy and 7 (16.3%) recurrences (3 vaginal vault, 2 pelvic, 2 distant) with external beam pelvic radiotherapy. The 5 year overall survival was 73.1% with vaginal vault brachytherapy vs 73.7% with external beam pelvic radiotherapy plus vaginal brachytherapy (p=0.31), the 5 year recurrence-free survival was 65.0% vs 68.2% (p=0.61), and the 5 year recurrence risk was 20.3% vs 19.4% (p=0.94). On univariable and multivariable analysis, only age was a statistically significant predictor for overall survival and recurrence-free survival (p<0.05), but not lymphovascular space invasion (HR, 2.97; 95% CI, 0.99 to 8.93 for overall survival, p=0.15). The type of adjuvant radiotherapy did not predict for recurrence (p=0.94). Conclusions: There was no significant difference in overall survival, recurrence-free survival, and recurrence risk between vaginal vault brachytherapy vs external beam pelvic radiotherapy plus vaginal vault brachytherapy in patients with stage II endometrial cancer.